2023
DOI: 10.3390/molecules28083345
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Process and Dynamic Changes in Triterpenoids of Lactuca indica from Different Medicinal Parts and Growth Periods

Abstract: In this study, the triterpenoids in the leaves of Lactuca indica L.cv. Mengzao (LIM) were extracted via microwave-assisted ethanol extraction, and the optimum extraction conditions for triterpenoids were determined through single-factor experiments and the Box–Behnken method. The effects of three factors (solid–liquid ratio, microwave power and extraction time) on the total triterpenoids content (TTC) were evaluated. The TTC of different parts (roots, stems, leaves and flowers) of LIM in different growth stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…The content of total triterpenoids was higher in the leaves than in the stems at different stages, which was consistent with Allium ursinum and Lactuca indica [35,36]. As the main organ for the transportation of nutrients, the canes provide a pathway for the synthesis and transportation of total triterpenoids, so the content of total triterpenoids is low.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The content of total triterpenoids was higher in the leaves than in the stems at different stages, which was consistent with Allium ursinum and Lactuca indica [35,36]. As the main organ for the transportation of nutrients, the canes provide a pathway for the synthesis and transportation of total triterpenoids, so the content of total triterpenoids is low.…”
Section: Discussionsupporting
confidence: 75%
“…The antioxidant capacity of triterpenoids is mainly related to the number and position of the hydroxyl groups on the carbon chain; C-9 and C-14 form a seven-membered carbocyclic core and have structures such as lactones [39,42,43]. In this study, the antioxidant capacity of the total triterpenoids in leaves was stronger than that in the canes, which may be due to the different types and contents of triterpenoid monomers, leading to differences in antioxidant capacity [35,36]. Studies have shown that the total triterpenoids of S. chinensis had a good therapeutic effect on oxidative cell damage induced by hydrogen peroxide, but their antioxidant capacity was weaker than that of lignans and stronger than that of polysaccharides [44,45].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The total flavonoid content (TFC), total terpenoid content (TTC), total phenolic content (TPC), and quinone content (QC) in GWH were determined by the NaNO 2 -Al(NO 2 ) 3 method (Tu et al, 2018), vanillin-Glacial acetic acid method (Hao et al, 2023), Folinol colorimetric method (Xiang et al, 2019), and spectrophotometric method (Qin et al, 2022), respectively, with minor modifications. Rutin, oleanolic acid, gallic acid, and quinone were used as standards, separately, and the absorbance was measured at their maximum absorption wavelengths.…”
Section: Determination Of Bioactive Compoundsmentioning
confidence: 99%